Effectiveness of Beta Vulgaris L (BIT) Juice To Increase Haemoglobin Levels In Pregnant Women Anemia at Primary Health Care Kotaraja - Sitti Zahyrah; Siana Dondi; Ika Wijayanti (Journal of Midwifery Science: Basic and Applied Research, 2020)
Anemia is the world's second leading cause of disability and because of that, it becomes one of the most serious global public health problems. Pregnant women who suffer from anemia are at risk of having miscarriage, babies born prematurely, low birth weight babies, and bleeding before and after delivery. This study aims to understand the effectiveness of giving beta vulgaris L (beet) fruit juice in increasing hemoglobin levels for anemic pregnant women. This research is a Quasi Experiment, using the Nonequivalent Control Group Design. The population in this study were 30 pregnant women who came for ANC examinations in October-December 2019. The sampling technique used was the total sampling technique. The data used for this research was the secondary data collected from the profile of the Jayapura City Health Office. Meanwhile, the primary data were collected using observation sheets and a digital haemometer. The analysis technique used was the Dependent T test (Paired Sample Test). This study showed the frequency distribution data before intervention, the level of mild anemia was 46.7% and moderate anemia was 53.3%. Based on the results of the Paired Sample T-Test, the value of p = 0.000 (p 0.05) was obtained.  Beta vulgaris L (beet) fruit juice is effective for increasing Hb levels of pregnant women with anemia. Keyword : Anemia, Beta Vulgaris L (Beet) juice, pregnant women, haemoglobin